Pengelolaan Wirausaha Mandiri Produk Kue Tradisional Berbasis Digital di KSU Berlian - Arianti, Gusmia; Tarsani, Oni; Rizqullah, Muhammad Shaddam (Journal of Servite, 2023)
Entrepreneurial Management of Traditional Cake Products based on Digital Cooperative Koperasi Serba Usaha (KSU) Berlian Pisangan Village Ciputat Timur Tangerang Selatan Banten aims to improve the management of traditional cake products of KSU Berlian members which includes training and assistance in packaging and branding methods, sales techniques and marketing management and entrepreneurship for members and management of cooperatives based on digital to improve community welfare. The problems found are less attractive product packaging designs, and marketing that has not been managed properly, by utilizing communication technology. The solution to deal with the problems offered by the Proposing Team is coaching provided to the community in the form of hard skills programs including product packaging design training to make it attractive and have selling value and marketing development training consisting of digital-based brands, sales and services. The training program was held on 26 May 2023 and 23 June 2023. The activities carried out were able to improve the management of traditional cake products of KSU Berlian members which included training and mentoring on packaging and brand methods, sales techniques and marketing management and entrepreneurship for members and management of digital-based cooperatives to improve community welfare